2022
DOI: 10.3389/fphys.2022.1062598
|View full text |Cite
|
Sign up to set email alerts
|

Toward improved understanding of foot shape, foot posture, and foot biomechanics during running: A narrative review

Abstract: The current narrative review has explored known associations between foot shape, foot posture, and foot conditions during running. The artificial intelligence was found to be a useful metric of foot posture but was less useful in developing and obese individuals. Care should be taken when using the foot posture index to associate pronation with injury risk, and the Achilles tendon and longitudinal arch angles are required to elucidate the risk. The statistical shape modeling (SSM) may derive learnt information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…An issue with 3D shapes and dynamic measurements is capturing the varying 3D shape over time, i.e., analysing a four-dimensional (4D) foot shape. Recent research has been promising in this area, and it is hoped that it continues to develop so foot morphology during gait can be compared to a general population for abnormalities, with footwear and treatment considerations from a functional perspective [ 51 , 52 ]. The use of 4D foot morphology assessment would also be beneficial for longitudinal analysis to assess if the foot develops as described here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An issue with 3D shapes and dynamic measurements is capturing the varying 3D shape over time, i.e., analysing a four-dimensional (4D) foot shape. Recent research has been promising in this area, and it is hoped that it continues to develop so foot morphology during gait can be compared to a general population for abnormalities, with footwear and treatment considerations from a functional perspective [ 51 , 52 ]. The use of 4D foot morphology assessment would also be beneficial for longitudinal analysis to assess if the foot develops as described here.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could compare 3D foot shape with injury and/or pain development in participants to discover if any foot morphological features are associated with risk of injury or pain. This could inform cut-offs and abnormal ranges for 3D foot morphology for clinicians, and work similar to Stanković et al for detecting abnormalities may streamline and standardise clinical assessment and treatment [ 51 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the shape of the foot is not static and can vary depending on individual characteristics. For example, foot shape morphs during dynamic running or walking situations, and its morphology variations may further result in shoes being ill-fitted, while ill-fitted footwear has been shown to be related to dermatologic problems 17 , 18 , 22 . On the other hand, the foot exhibits a sophisticated structure with a high density of sweat glands and intricate blood vessel orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, previous research identified that biomechanical models for normal-weight adults are inaccurate and unreliable for describing mechanics of adults with obesity [ 17 , 18 ]. As a result, obesity-specific marker sets incorporating additional reflective and digitized markers around the pelvis have been established to more accurately measure gait biomechanics with OMC in this population [ 17 ].…”
Section: Introductionmentioning
confidence: 99%